Application of Remote sensing and Geo-Spatial Techniques for Land use Land Cover Mapping and Change Detection of Bhavnagar Municipal Corporation Area, Gujarat - Kamboj, R. D.; Patel, Rajal; Patel, Nitin; Gohil, Mitesh (International Journal of Scientific Research in Civil Engineering, 2020)
Remote sensing and Geographic Information System (GIS) are one of the detailed and useful ways to develop land use classification maps. It vastly improves the selection of areas designated as forest, tree cover, industrial and/or urban zones of a region. The present study has been carried out in Bhavnagar Municipal Corporation (BMC) to detect change in land use land cover from 2005 to 2016, as new developments (agriculture, commercial, industrial and urban) are emerging from time to time. Maps and land records obtained from Bhavnagar Municipal Corporation and the remote sensing data of Resource Sat-2, LISS-IV for the year 2005, 2011 and 2016 data were used for interpreting the quantitative data of spatial and temporal dynamics in the study area. Based on geographical conditions, remote sensing data and field survey, the study area was classified into seven categories. The increase was observed in salt pan (+152.73%), water bodies (80.84%), dense tree cover (21.08%), open tree cover (7.21%) and built up area (38.36%), whereas, the salt affected area (63.39%) and open land area (6.50%) decreased over the study period.  The driving force behind this change was economic development, rapid urbanization and industrialization along with extensive population growth.
Keywords: Bhavnagar; Change Detection; GIS; Gujarat; Land Use/land Cover; Remote Sensing